Hubungan Hygiene Sanitasi dengan keberadaan Bakteri Eschericia Coli pada Minuman Es Kelapa Muda : Hubungan Hygiene Sanitasi dengan Keberadaan Bakteri Eschericia Coli pada Muniman Es Kelapa Muda - Nurafni Maftukhah (IKesT Muhammadiyah Palembang, 2025)
Background: Young coconut ice drink is one of the drinks that are most sought after by the public, if in the management of unhygienic and sanitary drinks can cause the ingredients in food drinks that can cause health problems for consumers. Purpose: This study aims to analyze the relationship of sanitary hygiene with the presence of Escherichia Coli bacteria in Young Coconut Ice drinks. Method: This type of research is a research in the form of experiments taken from literature studies. Data collection by observation, interview, questionnaire and laboratory examination. Data analysis using statistical tests with Chi-square test to analyze the relationship of sanitation hygiene with the presence of Escherichia Coli bacteria in young coconut ice drinks. Result: The results of this study indicate a relationship of sanitary hygiene with the presence of Escherichia coli bacteria by showing a value (p<0.05) while from laboratory results as much as 80% of all samples of positive young coconut ice drinks Escherichia Coli and 20% of samples of young coconut ice drinks negative Escherichia Coli, especially in processing raw materials as many as 3 traders who met the hygiene sanitation requirements and 16 traders who did not meet the hygiene requirements sanitation. Conclusion: There is a relationship between sanitation hygiene and the presence of bacteria Escherichia Coli in young coconut iced drinks, The research results show that there are still many iced drinks available young coconuts that are positive for containing Escherichia Coli bacteria are suitable with RI Minister of Health Regulation No. 492/Menkes/PER/IV/2010 concerning Requirements Drinking Water Quality is 0 per 100 ml sample, The results of this research show that in terms of sanitation hygiene principles there are still those who do not meet the sanitation hygiene requirements, especially for processing of raw materials in accordance with the Republic of Indonesia Minister of Health Decree No. 942/Menkes/SK/VII/2003 Guidelines for Sanitation Hygiene Requirements Snack Food.Keywords: Sanitation Hygiene, Young Coconut Ice, Escherichia Coli